Antropocentrični pristup mediološko-komunikološko-sociološkim reperkusijama digitalne revolucije / Approach to Mediological-Communication-Sociological Repercussion of the Digital Revolution (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text is a review of a book by Andrew Keen How to Fix the Future: Staying Human in the Digital Age, Zagreb: Naklada Ljevak, 2018.